Papio Baboon Species Indicative Alu Elements. (14th July 2017) - Walker, Jerilyn A.; Jordan, Vallmer E.; Steely, Cody J.; Beckstrom, Thomas O.; McDaniel, Cullen L.; St. Romain, Corey P.; Bennett, Emily C.; Robichaux, Arianna; Clement, Brooke N.; Konkel, Miriam K.; ,; Batzer, Mark A.
Abstract: The genus of Papio (baboon) has six recognized species separated into Northern and Southern clades, each comprised of three species distributed across the African continent. Geographic origin and phenotypic variants such as coat color and body size have commonly been used to identify different species. The existence of multiple hybrid zones, both ancient and current, have complicated efforts to characterize the phylogeny of Papio baboons. More recently, mitochondrial DNA (mtDNA) and Y-chromosome genetic markers have been utilized for species identification with particular focus on the hybrid zones. Alu elements accumulate in a random manner and are a novel source of identical by descent variation with known ancestral states for inferring population genetic and phylogenetic relationships. As part of the Baboon Genome Analysis Consortium, we assembled an Alu insertion polymorphism database of nearly 500 Papio -lineage specific insertions representing all six species and performed population structure and phylogenetic analyses. In this study, we have selected a subset of 48 species indicative Alu insertions and demonstrate their utility as genetic systems for the identification of baboon species within Papio . Individual elements from the panel are easy to genotype and can be used in a hierarchical fashion based on the original level of uncertainty. This Alu- 48 panel should serve as a valuable tool during the maintenance of pedigree records in captive populations and assist in the forensic identification of fossils and potential hybrids in the wild.